Clinical Significance of Long Non-Coding RNA SNHG5 in the Diagnosis and Prognosis of Chronic Obstructive Pulmonary Disease - Xue-Ting Yao; Wen-Ping Feng; Zhi-Peng Gong; Xin-Peng Li (COPD)
Chronic obstructive pulmonary disease (COPD) is preventable and requires early screening. The study aimed to examine the clinical values of long non-coding RNA (lncRNA) SNHG5 in COPD diagnosis and prognosis. Out of 160 COPD patients, 80 were in the stable stage and 80 were in the acute exacerbation of COPD stage (AECOPD). SNHG5 expression was detected via qRT-PCR. The survival analysis was conducted using Cox regression analysis and K-M curve. SNHG5 levels significantly reduced in both stable COPD and AECOPD groups compared with the control group, with AECOPD group recording the lowest values. SNHG5 levels were negatively correlated with GOLD stage. Serum SNHG5 can differentiate stable COPD patients from healthy individuals (AUC = 0.805), and can screen AECOPD from stable ones (AUC = 0.910). SNHG5 negatively influenced the release of inflammatory cytokines. For AECOPD patients, those with severe cough and wheezing dyspnea symptoms exhibited the lowest values of SNUG5. Among the 80 AECOPD patients, 16 cases died in the one-year follow-up, all of whom had low levels of SNHG5. SNHG5 levels independently influenced survival outcomes, patients with low SNHG5 levels had a poor prognosis. Thus, lncRNA SNHG5, which is downregulated in patients with COPD (especially AECOPD), can potentially protect against AECOPD and serve as a novel prognostic biomarker for AECOPD.